2020
DOI: 10.1074/jbc.ra118.005616
|View full text |Cite
|
Sign up to set email alerts
|

A kinesin adapter directly mediates dendritic mRNA localization during neural development in mice

Abstract: Motor protein-based active transport is essential for mRNA localization and local translation in animal cells, yet how mRNA granules interact with motor proteins remains poorly understood. Using an unbiased yeast two–hybrid screen for interactions between murine RNA-binding proteins (RBPs) and motor proteins, here we identified protein interaction with APP tail-1 (PAT1) as a potential direct adapter between zipcode-binding protein 1 (ZBP1, a β-actin RBP) and the kinesin-I motor complex. The amino acid sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 92 publications
(98 reference statements)
1
23
0
Order By: Relevance
“…In neurons, RNPs are actively transported along microtubules by the motor proteins kinesin and dynein, and these interactions are mediated by protein-based (Baumann et al, 2020; Dictenberg et al, 2008; Wu et al, 2020) or vesicular adaptors (Cioni et al, 2019; Liao et al, 2019). Properly regulated microtubule-based RNP transport and local translation are important to prevent neurological disease, which is often caused by mutations to microtubule associated proteins (Deniston et al, 2020; Dubey et al, 2015), motor proteins and adaptors (Hirokawa et al, 2010; Liao et al, 2019; Nicolas et al, 2018; Zhao et al, 2001), RBPs (Fernandopulle et al, 2021; Ramaswami et al, 2013), and regulators of translation (Banerjee et al, 2018; Kapur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, RNPs are actively transported along microtubules by the motor proteins kinesin and dynein, and these interactions are mediated by protein-based (Baumann et al, 2020; Dictenberg et al, 2008; Wu et al, 2020) or vesicular adaptors (Cioni et al, 2019; Liao et al, 2019). Properly regulated microtubule-based RNP transport and local translation are important to prevent neurological disease, which is often caused by mutations to microtubule associated proteins (Deniston et al, 2020; Dubey et al, 2015), motor proteins and adaptors (Hirokawa et al, 2010; Liao et al, 2019; Nicolas et al, 2018; Zhao et al, 2001), RBPs (Fernandopulle et al, 2021; Ramaswami et al, 2013), and regulators of translation (Banerjee et al, 2018; Kapur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…RBPs within the granule can interact with the motors either directly or via adaptor proteins (Figure 2; Kanai et al, 2004;Hirokawa, 2006;Kiebler and Bassell, 2006;Davidovic et al, 2007;Dictenberg et al, 2008). Transport of mRNAs that encode the key plasticity proteins, such as CaMKII (CaMKIIa) and β-Actin (ActB), occurs via this mechanism on microtubule tracks (Tiruchinapalli et al, 2003;Mikl et al, 2011;Wu et al, 2020). In contrast, short-range trafficking of RNA granules is mediated by myosin motors on F-actin filaments (Figure 2).…”
Section: Transport Of Mrna To Remote Neuronal Compartmentsmentioning
confidence: 99%
“…To support this notion, Liao et al (2019) observed the LAMP1-ANXA11 association in dendrites in addition to axons, hinting that lysosomal hitchhiking for long-range transport could also exist in the dendritic arbor. Other outstanding questions include how a particular transport strategy is selected: β-actin mRNA is trafficked by both conventional trafficking mechanisms and vesicular hitchhiking (Liao et al, 2019;Wu et al, 2020), suggesting that a given mRNA could be transported by either mode of transport. Understanding under what physiological circumstances (e.g., certain types of plasticity, cell stress) these transport itineraries are selected will be imperative to fully define the process of RNA granule trafficking to synapses.…”
Section: Long-range Rna Transport Via Endosomes/lysosomesmentioning
confidence: 99%
“…Microdissection and TRAP approaches for isolating RNA have revealed important roles for transcript UTR sequence motifs and transcript trafficking proteins in local translation. mRNAs are transported in phase-separated ribonucleoprotein (RNP) granules over long distances to dendrites and axons to establish local transcriptome pools (Nalavadi et al, 2012;Jung et al, 2014;Das et al, 2019;Liao et al, 2019;Pushpalatha and Besse, 2019;Fukuda et al, 2020;Rhine et al, 2020;Wu et al, 2020; Figure 3). The spatial control of transcript trafficking is based on mRNA sequences found in 3 and 5 untranslated regions (UTRs; Figure 3A) that act as binding sites for trans-acting RBPs (Sahoo et al, 2018;Bae and Miura, 2020).…”
Section: Local Transcriptomes/translatomes Are Precisementioning
confidence: 99%